2012
DOI: 10.1165/rcmb.2011-0332oc
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-α and Arginase I Mediate Pneumolysin-Induced Pulmonary Endothelial Hyperpermeability

Abstract: Antibiotics-induced release of the pore-forming virulence factor pneumolysin (PLY) in patients with pneumococcal pneumonia results in its presence days after lungs are sterile and is a major factor responsible for the induction of permeability edema. Here we sought to identify major mechanisms mediating PLY-induced endothelial dysfunction. We evaluated PLY-induced endothelial hyperpermeability in human lung microvascular endothelial cells (HL-MVECs) and human lung pulmonary artery endothelial cells in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
91
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 52 publications
(71 reference statements)
2
91
0
Order By: Relevance
“…In previous studies, our research group and other investigators have demonstrated that the lectin-like domain of TNF represents a potent stimulator of ALC in several mammalian species and involves activation of ENaC via an unknown mechanism (21,24,(27)(28)(29)(30)(31)38) . This study was designed to determine the mechanism by which the lectin-like domain of TNF can promote ENaC activity.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In previous studies, our research group and other investigators have demonstrated that the lectin-like domain of TNF represents a potent stimulator of ALC in several mammalian species and involves activation of ENaC via an unknown mechanism (21,24,(27)(28)(29)(30)(31)38) . This study was designed to determine the mechanism by which the lectin-like domain of TNF can promote ENaC activity.…”
Section: Discussionmentioning
confidence: 92%
“…Yet, this dose allowed us to specifically investigate the effect of TIP on PLY-induced impairment of ALC rather than on barrier function. Moreover, we have previously shown that the TIP peptide possesses barrier-protective effects in permeability edema induced by instillation of higher doses of PLY (30).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…At higher lytic concentrations, PLY directly causes tissue damage by means of its transmembrane pore-forming properties (14,26,38,42). In this regard, a recent study identified protein kinase C-␣ and arginase 1 as important mediators to contribute to PLY-induced pulmonary endothelial dysfunction (32). Thus, a direct cytolytic effect of PLY represents one possible mechanism by which S. pneumoniae may have caused lung leakage in Flt3L-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic deletion of PLY from S. pneumoniae results in reduction of virulence by several orders of magnitude (23)(24)(25). In addition, PLY has been reported to be a critical virulence factor involved in pneumonia, acute lung injury, and pulmonary permeability edema (26)(27)(28)(29). Hla is another PFT expressed in many strains of S. aureus.…”
mentioning
confidence: 99%